Non-operative management of an isolated lateral collateral ligament injury in an adolescent patient and review of the literature. (15th May 2018) - Davenport, Dominic; Arora, Ajay; Edwards, Max R
Abstract : We present a rare case of isolated traumatic pure ligamentous rupture of the lateral collateral ligament of the knee in an adolescent high-level footballer managed non-operatively with a good functional outcome and return to sport in 4 months.